Computational fluid-structure interaction : methods and applications - Bazilevs, Yuri.; Takizawa, Kenji; Tezduyar, Tayfun E. (Chichester, West Sussex, UK : Wiley, A John Wiley & Sons, Publication, 2013)
"Computational Fluid-Structure Interaction is a complete, self-contained reference that takes the reader from the fundamentals of computational fluid and solid mechanics all the way to the state-of-the-art in CFSI research"--
3.2 NURBS Basis Functions, Curves, Surfaces, and Solids3.3 h-, p-, and k-Refinement of NURBS Meshes; 3.4 NURBS Analysis Framework; Chapter 4 ALE and Space-Time Methods for Moving Boundaries and Interfaces; 4.1 Interface-Tracking (Moving-Mesh) and Interface-Capturing (Nonmoving-Mesh) Techniques; 4.2 Mixed Interface-Tracking/Interface-Capturing Technique (MITICT); 4.3 ALE Methods; 4.4 Space-Time Methods; 4.5 Advection-Diffusion Equation; 4.5.1 ALE Formulation; 4.5.2 Space-Time Formulation; 4.6 Navie-Stokes Equations; 4.6.1 ALE Formulation.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Fluid-structure interaction -- Data processing; Fluid-structure interaction -- Mathematical models; Fluid-structure interaction -- Data processing; Fluid-structure interaction -- Mathematical models; TECHNOLOGY & ENGINEERING -- Drafting & Mechanical Drawing; TECHNOLOGY & ENGINEERING -- Drafting & Mechanical Drawing; Fluid-structure interaction -- Data processing; Fluid-structure interaction -- Mathematical models; Electronic books; Electronic books